(3TQM Md GdNdGUI aj Yde GdMSGHs - (3QeVGf Hf CHi gQjQI GdLRQj GdbGOQis ((3eMeO Hf GdSjO MSf BeOi s)
(3ChdgG (B:s
(3CMeOc jG ef CYOGO fYeg dGJMUi hHYO ajbhd GdabjQ Edi CdWGa QHg GdZfi QeVGf GHf CHj gQjQI deG cGfJ GdQSGdI GdeSeGI HNdGUI GdMSGH ddHGQY HgGA GdOjf GdMSfi QSGdI MGhjI ddCJe ef GdCUhd s
(3BNQgG (B:s
( (3aQZ efgG (B) (3GdabjQ Edjg SHMGfg QeVGf GHf CHj gQjQI GdLRQi GdbGOQi UMhI GdCMO ef ChGNQ GdTgQ GdeHGQc LeGOi GdChdi dSfI Cda hEKfjf hJSYjf ef GdgLQI s
(3GdUaMGJ eQbeI JQbje MOjKs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs